Pengaruh Edukasi terhadap Dukungan Keluarga dalam Pengelolaan Hipertensi pada Lansia di UPTD Puskesmas Jekan Raya, Palangka Raya - Naniek Sukesie; Karmitasari Yanra Katimenta; Meilitha Carolina; Septian Mugi Rahayu (PPNI UNIMMAN, 2024)
Education is an independent nursing intervention designed to help individuals, groups, or communities, including hypertension patients, address their health issues through learning activities, with nurses acting as educators. Hypertension is a chronic disease often referred to as the